Effects of Radiation on Materials: 12th International Symposium Volume II 1985
DOI: 10.1520/stp87019850021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Irradiation Hardening and Embrittlement of Pressure Vessel Steels

Abstract: Based on a large body of test and power reactor data, empirical relationships between irradiation strengthening and embrittlement are derived. It is shown that the Charpy V-notch (Cv) 41-J indexed transition temperature increases and the upper-shelf energy decreases systematically with increases in the yield stress. The transition temperature shifts are related to two mechanisms: (1) increases in the maximum temperature of elastic-cleavage fracture, and (2) decreases in the slope of the Cv energy versus test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The relationships between ∆YS and changes in the Charpy test properties from the US irradiated pressure vessel steel database were reported by a previous investigation [11]. It is worth noting the results in order to analyze the relationship in Korean LWR materials.…”
Section: Irradiation Embrittlement and Strengtheningmentioning
confidence: 80%
See 3 more Smart Citations
“…The relationships between ∆YS and changes in the Charpy test properties from the US irradiated pressure vessel steel database were reported by a previous investigation [11]. It is worth noting the results in order to analyze the relationship in Korean LWR materials.…”
Section: Irradiation Embrittlement and Strengtheningmentioning
confidence: 80%
“…However, Odette et al reported that no particular effect of T41J on the proportional coefficient between ∆YS and TTS was found in the EPRI database, whereas test reactors data appeared to show a rather systematic trend of higher values in the proportional coefficient with increasing initial T41J, as well as with increasing ∆YS [11]. For the data group with high initial transition temperatures (-5 to -20°C), the proportional coefficient was ~0.65, about 50% higher than the corresponding value (~0.43) for the data group with low initial transition temperatures (-70 to -40°C) [13][14][15][16][17].…”
Section: Empirical Trends In Us Rpv Steelsmentioning
confidence: 95%
See 2 more Smart Citations
“…The TTS implications of LBP and transformation of CRPs to Mn-Ni-Si dominated features are increasing TTS with increasing neutron fluence, results not predicted by models based on surveillance data at relatively low fluences. References [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] were used variously for much of the preceding discussion.…”
Section: Radiation Damage Mechanismsmentioning
confidence: 99%